THE INFLUENCE OF JOB STRESS ON WORK PROCRASTINATION WITH THE LEVEL OF JOB SATISFACTION AS AN INTERVENING VARIABLE ON MEMBERS OF THE BRIMOB BATTALION B PIONEER SENTOLO, KULON PROGO - Mahardata, W. Dika Pradana; Chasanah, Uswatun (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2024)
Work stress is a condition of tension experienced by employees in the face of work and creates a physical / psychological imbalance, and affects the emotions, thought processes and conditions of an employee which can cause harm to individuals and related organizations. Procrastination is a delay of a few moments before the deadline or a long-term delay to exceed the deadline so that it interferes with performance within a limited time span by replacing activities that are not so important. Job satisfaction refers to an individual's general attitude towards his or her job. Job satisfaction is the result of employees' perceptions of the extent to which their work can provide such an emotional state. This study aims to empirically examine the effect of job stress on work procrastination with job satisfaction as an intervening variable in members of Brimob Battalion B Pelopor, Sentolo, Kulon Progo. This research was conducted at Mako Brimob Battalion B Pelopor, Sentolo, Kulon Progo. The sample used amounted to 50 people. The method in this study uses quantitative methods. Data collection methods using interviews and questionnaires. The analysis method used is Partial Least Square (PLS) which uses the results of the outer model and inner model tests. Based on the results of the study, the following findings were obtained: work stress has a positive and significant effect on work procrastination, work stress has a positive and significant effect on job satisfaction, job satisfaction has a positive and insignificant effect on work procrastination, work stress has an insignificant effect and a direct effect on work procrastination with job satisfaction.